Literature Review: Pengaruh Model Problem Based Learning terhadap Kemampuan Numerasi Murid Pada Pembelajaran Biologi: (Literature Review: The Effect of Problem-Based Learning Model on Students' Numeracy Skills in Biology Learning) - Atika, Fadhilla; Syamsurizal , Syamsurizal (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
The development of science and technology in the 21st century requires students to possess higher-order thinking skills, problem-solving abilities, and numeracy literacy applicable to real-life contexts. In biology learning, numeracy is not limited to basic calculation skills but also includes the ability to interpret data, read graphs, and analyze quantitative relationships between variables. However, the 2022 PISA results indicate that Indonesian students’ numeracy achievement remains low, highlighting the need for instructional approaches that systematically integrate biological concepts with numerical skills. This article aims to review and synthesize research findings on the implementation of Problem Based Learning (PBL) in biology education and its relevance to strengthening students’ numeracy skills. This study employs a literature review method using content analysis of national and international articles published between 2022 and 2025, obtained through Google Scholar and other relevant academic journals. The findings reveal that PBL consistently has a positive impact on improving numeracy literacy, critical thinking skills, and student engagement through contextual problem-solving and data analysis activities. Therefore, the integration of PBL in biology learning has the potential to serve as an effective strategy to enhance numeracy skills in line with the demands of 21st-century competencies. Abstrak. Perkembangan ilmu pengetahuan dan teknologi abad ke-21 murid menuntut memiliki kemampuan berpikir tingkat tinggi, pemecahan masalah, serta literasi numerasi yang aplikatif dalam kehidupan nyata. Numerasi dalam pembelajaran biologi tidak hanya berkaitan dengan kemampuan berhitung, tetapi juga mencakup keterampilan menginterpretasi data, membaca grafik, dan menganalisis hubungan kuantitatif antarvariabel. Namun, hasil PISA 2022 menunjukkan capaian numerasi peserta didik Indonesia masih rendah, sehingga diperlukan pendekatan pembelajaran yang mampu mengintegrasikan konsep biologi dengan keterampilan numerik secara sistematis. Artikel ini bertujuan untuk mengkaji dan mensintesis hasil penelitian terkait penerapan Problem Based Learning (PBL) dalam pembelajaran biologi serta relevansinya terhadap penguatan kemampuan numerasi. Penelitian ini menggunakan metode tinjauan pustaka dengan analisis isi terhadap artikel nasional dan internasional terbitan tahun 2016–2026 yang diperoleh melalui Google Scholar dan jurnal relevan lainnya. Hasil kajian menunjukkan bahwa PBL secara konsisten memberikan dampak positif terhadap peningkatan literasi numerasi, berpikir kritis, dan keterlibatan peserta didik melalui aktivitas pemecahan masalah kontekstual dan analisis data. Dengan demikian, integrasi PBL dalam pembelajaran biologi berpotensi menjadi strategi efektif untuk mendukung penguatan numerasi sesuai kebutuhan kompetensi abad ke-21.